2022
DOI: 10.3390/ijerph191811551
|View full text |Cite
|
Sign up to set email alerts
|

Job Mobility and Subjective Well-Being among New-Generation Migrant Workers in China: The Mediating Role of Interpersonal Trust

Abstract: New-generation migrant workers refers to those born in 1980 or thereafter, who become the majority of rural–urban migrants. New-generation migrant workers in Chinese cities are struggling with a lack of urban resources, which may lead to low well-being. On the basis of a questionnaire survey of 203 new-generation migrant workers, we used a multiple regression analysis to study new-generation migrant workers’ well-being and the mechanism underlying the effect of job mobility on well-being. The job mobility scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the early stages of migration, the older migrants have a lower level of social adjustment and the stress of the external environment can have a greater impact on their psychological well-being. Zhang confirmed in his study that the length of time since migration positively predicted positive mood [ 45 ]. Liu also found that older migrants who had migrated more than 10 years prior reported better subjective well-being than they had experienced in their place of origin [ 46 ], and over time, the unfamiliar environment’s barriers to adaptation gradually decrease, the level of social integration continued to increase, and their mental health improved [ 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…In the early stages of migration, the older migrants have a lower level of social adjustment and the stress of the external environment can have a greater impact on their psychological well-being. Zhang confirmed in his study that the length of time since migration positively predicted positive mood [ 45 ]. Liu also found that older migrants who had migrated more than 10 years prior reported better subjective well-being than they had experienced in their place of origin [ 46 ], and over time, the unfamiliar environment’s barriers to adaptation gradually decrease, the level of social integration continued to increase, and their mental health improved [ 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…Intergenerational difference is an important perspective in the study of rural migrant workers. Previous studies have divided rural migrant workers into two groups, the “old generation” and the “new generation,” based on whether they were born before or after 1980 ( 51 ). The “old generation” typically has lower levels of knowledge, skills, education, and weaker health conditions compared to the “new generation” ( 52 ).…”
Section: Resultsmentioning
confidence: 99%